Adaptogens in chemobrain (Part II): effect of plant extracts on chemotherapy-induced cytotoxicity in neuroglia cells - Seo, Ean-Jeong; Klauck, Sabine; Efferth, Thomas; Panossian, Alexander (Phytomedicine, 2019)
BACKGROUND: Cancer chemotherapy-induced cognitive impairments are apparently associated with harmful effects on physiological functions of brain cells. Adaptogens, are known to exhibit neuroprotective effects and to increase cognitive functions in clinical studies. In our previous study (Seo et al., 2018), we demonstrated that selected adaptogenic extracts significantly attenuate cytostatic-induced regulation of more than 100 genes involved in the activation of neuronal death and inhibiting neurogenesis. Neuroprotective and cytoprotective activities of adaptogens rise the question about their possible impact on cytostatic effects of a chemotherapeutic combination of 5-fluorouracil, epirubicin and cyclophosphamide (FEC). - AIM: The aim of this study was to assess the effects of selected adaptogenic herbal extracts, namely of andrographolide (AND), Herba Andrographidis (AP), Radix Eleutherococci (ES) genuine extracts, their fixed combination (AE), and the combination of three adaptogenic herbs, Rhodiola Radix, Shisandra Fructus and Eleutherococci Radix (RSE) on the cytotoxicity of a fixed combination of 5-fluorouracil, epirubicin and cyclophosphamide (FEC) on neuroglia cells. - METHODS: Cytotoxicity of FEC, adaptogenic extracts and their combination with FEC was tested on isolated T98G cells in a wide range of concentrations of all tested compounds. - RESULTS: FEC reproducibly inhibited the proliferation of T98G cells by 50% at concentrations of 5×10-1µg/ml epirubicin, 500×10-1µg/ml 5-fluorouracil and 20×10-1µg/ml 4-hydroperoxycyclophosphamide after 24h incubation of cells. These concentrations were subsequently used for experiments with adaptogenic extracts. The cytotoxic activity of FEC was not significantly changed in the presence of AND, ES and AE. Furthermore, it was potentiated by AP extract and RSE in concentrations of 0.06-6µg/ml and 17.6-26.4µg/ml. - CONCLUSION: The neuroprotective effect of adaptogens did not attenuate the cytotoxic activity of FEC. Application of cytostatic drugs in combination with adaptogenic plant extracts likely have no impact in cytotoxic effect of FEC. Furthermore, AP and RSE potentiated the cytotoxic effects of FEC.